Cervical spine immobilization in patients with a geriatric facial structure: the influence of a geriatric mandible structure on the immobilization quality using a cervical collar - Jung, Matthias; Grützner, Paul Alfred; Schneider, Niko; Keil, Holger; Kreinest, Michael (Geriatric Orthopaedic Surgery & Rehabilitation, 2021)
Introduction:Demographic changes have resulted in an increase in injuries among geriatric patients. For these patients, a rigid cervical collar is crucial for immobilizing the cervical spine. However, evidence suggests that patients with a geriatric facial structure require a different means of immobilization than patients with an adult facial structure. This study aimed to analyze the remaining motion of the immobilized cervical spine based on facial structure.Materials and Methods:This study was performed on 8 fresh human cadavers. Facial structure was evaluated via ascertaining the mandibular angle by computer tomography. A mandibular angle below 130°, belongs to the adult facial structure group (n = 4) and a mandibular angle above 130°, belongs to the geriatric facial structure group (n = 4). The flexion and lateral bending of the immobilized cervical spine were analyzed in both groups using a wireless motion tracker system.Results:A flexion of up to 19.0° was measured in the adult facial structure group. The mean flexion in the adult vs. geriatric facial structure groups were 14.5° vs. 6.5° (ranges: 9.0-19.0 vs. 5.0-7.0°), respectively. Thus, cervical spine motion was (p = 0.0286) significantly more reduced in the adult facial structure group. No (p = 0.0571) significant difference was oberserved in the mean lateral bending of the adult facial structure group (14.5°) compared to the geriatric facial structure group (7.5°).Conclusion:Emergency medical service personnel should therefore follow current guidelines and recommendations and perform cervical spine immobilization with a cervical collar, including in patients with a geriatric facial structure.
Gesehen am 25.10.2021